Accrual-Based Accounting Information System with Break Even Point (BEP) Approach - Kadek Nonik Erawati (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2026)
The digital transformation of financial management is essential for modern business sustainability. However, traditional cash-based systems fail to represent true financial positions, while existing accounting software often lacks integrated managerial analytics tools. This creates a functional disconnect where managers must perform manual, error-prone calculations to determine profitability thresholds. To address this, this research develops a web-based Accrual Accounting Information System integrated with a dynamic Break Even Point (BEP) approach. The system automates the double-entry recording process and real-time classification of fixed costs from the general ledger to visualize safety margins instantly. The primary contribution of this study is the unification of professional accounting standards (PSAK) with strategic decision-support algorithms in a single platform. Evaluation using Black Box testing confirms the system achieves 100 percent accuracy in generating financial statements and BEP metrics, while usability analysis demonstrates that the responsive architecture significantly enhances workflow efficiency across devices. The results indicate that the system effectively transforms passive financial data into actionable insights, empowering proactive decision-making. Future work aims to incorporate machine learning for dynamic semi-variable cost analysis to further refine predictive capabilities.